Optical quasi flux density of Heisenberg ferromagnetic spin with qHATM approach - Korpinar, Talat; Korpinar, Zeliha; Demirkol, Ridvan Cem; Yeneroglu, Mustafa (Elsevier Gmbh, 2021)
In this paper, we construct new approach of optical quasi magnetic Lorentz flux of quasi normal magnetic flows of quasi-nq magnetic particle by quasi directional frame in 3D space. Thus, we get new conditions for optical quasi magnetic Lorentz flux for quasi-nq magnetic particle with quasi directional frame fields. Also, we get quasi magnetic Lorentz flux by quasi fields. Moreover, we derive new characterizations for optical quasi potentials of quasi normal magnetic flows by considering Heisenberg ferromagnetic spin. Optical magnetic flux surface is demonstrated in an uniform magnetic surface by using fractional optical and numerical results. The resulting optical quantities of quasi-nq magnetic particle are constructed numerically, discussed, and graphically offered for a new fractional equation of an optical quasi flux density.
Keywords: Quasi directional frame; Laplace transform (LT); q-Homotopy analysis transform method; Optical quasi normal magnetic flows; Heisenberg ferromagnetic spin; Optical flux density